Long-Run Performance of Private-Equity-Backed Initial Public Offering in the Southeast Asian Markets - Ariando, Heribertus; Nainggolan, Yunieta Anny (Journal of Business and Management, 2016)
Abstract— Over the past decade, the number of private-equity (PE) investments grew across the Southeast Asian markets, which was due to its rapid economic growth and lesser competition. However, while some believe that this has a positive impact to the economy, the real contribution of PE-backed transactions is unclear, as there is no study yet observing the nature of these transactions that specifically focuses on the Southeast Asian markets.This 6-month study examines the long-run stock performance of PE-backed initial public offering (IPO), by examining the historical data from the period of 1996 to 2016. This research uses market-adjusted and risk-adjusted returns to calculate the long-term stock returns. The result indicates although the performance of PE-backed IPOs differs in every market, generally, it underperforms almost all indices. However, it is less underperformed than the paired non-PE-backed IPO.This study aims to give an outlook of how a PE-backed IPO performs in the market. The finding is hoped to deliver some insights for financial sponsors, issuing firms, underwriters, and investors regarding the nature of the transactions in the Southeast Asian markets.Keywords: private equity, initial public offering, capital market, security performance, Southeast Asia.